Advantages of Combined Use of Claw Hooks and Sublaminar Wires as the Upper Foundation of Long Fixation from the Thoracic Spine to the Pelvis in Osteoporotic Cases: A Finite Element Analysis of Proximal Junction Stress - Takuhei Kozaki; Takachika Shimizu; Akimasa Murata; Ryuichiro Nakanishi; Takahiro Kozaki; Ei Yamamoto; Shunji Tsutsui; Mamoru Kawakami; Hiroshi Yamada (Spine Surgery and Related Research)
Introduction: This study aimed to compare the biomechanical stress at the proximal junctional aspect between the conventional pedicle screw (PS) fixation (PSF) and the low PS density fixation (LPF) method. Methods: This study involved 10 patients, half of whom have non-osteoporosis and the other half have osteoporosis. We made two types of intact models (one is from the upper thoracic-to-pelvis model, and the other is from the lower thoracic-to-pelvis model). From the intact models, we constructed two kinds of fusion models: (1) PSF and (2) LPF. The LPF method was as follows: The claw hooks (the combination of the down-going transverse process hooks and facet hooks) were set at the upper instrumented vertebra (UIV) and sublaminar wires at the thoracic spine and PSs at the lumbo-pelvis. Results: Upper thoracic to pelvis fixation model In non-osteoporosis, no significant difference between the PSF and LPF is found. In osteoporosis, the von Mises stresses of the vertebra body at UIV, UIV+1, and disc were significantly lower in LPF than in PSF. Lower thoracic-to-pelvis fixation model In non-osteoporosis, the average von Mises stress of the vertebral body at UIV+1 and the maximum stress at UIV were lower in LPF than in PSF; however, no significant difference was found in the others. In osteoporosis, the von Mises stress was significantly lower in LPF than in PSF. Conclusions: The claw hooks stabilized the vertebra body at UIV firmly, and sublaminar wires reduced load translation from the fixed spine.